Global Attractor for Weakly Damped Nonlinear Schrodinger-Boussinesq Equations in an Unbounded Domain (Journal of Partial Differential Equations, 2000)
In this paper the authors consider the Cauchy problem of nonlinear Schrödinger-Boussinesq equations in R and prove the existence of the maximal attractor.
Keywords: Nonlincar Schrödinger-Boussinesq; bounded absorbing set; decomposition of operator; maximal attractor